Modelling of carbon nanotubes with different structures at millimeters wavelength antennas - Jurn, Yaseen Naser (School of Computer and Communication Engineering, 2017)
The specific research objectives are addressed as follows; to investigate and study the EM properties of SWNT and B-SWNTs using nano solid tube material (NSTM) and single conductor material (SCM) modelling approach, respectively by EMETS CST (MWS) software package; to present the simple matching approach for the SWNTs and B-SWNTs dipole antennas based on optimization of loop (SMA-OPL) technique; to examine and compare the EM properties of the new structure material (PSM) for SWNT and B-SWNTs based composite which coated with graphite, copper, and silver using Equivalent Bulk Material (E-BM) approach. Mathematical and simulation modelling approach using the EMETS CST (MWS) for the SWNTs and B-SWNTs-composite materials were proposed and developed.